The Relationship between Serum Calcium Level and Risk Factor of Pregnancy-Induced Hypertension: A Meta-Analysis - Song, Yu-Xin; He, Lian-Ping; Li, Cui-Ping (Clinical and experimental obstetrics & gynecology, 2023)
Background: The relationship between serum calcium levels and pregnancy-induced hypertension is controversial. This work aimed to evaluate the relationship between serum calcium levels and the risk of pregnancy-induced hypertension. Methods: The following database: Chinese National Knowledge Infrastructure and PubMed, were searched to identify articles on the relationship between serum calcium levels and pregnancy-induced hypertension. The meta-analysis was conducted by using Review Manager (RevMan) [Computer program]. Results: A total of twenty one articles included in the present study. The meta-analysis revealed that patients with pregnancy-induced hypertension (PIH) had lower calcium levels (standardized weighted mean difference (SMD) = –0.68; 95% (–0.79, –0.56); p < 0.05). Conclusions: Our study suggests that serum calcium levels may be associated with the risk of pregnancy-induced hypertension.